The Impact of HOT Skills on Enhancing Professional Communication Strategies among Malaysian TESL Students - Azar, Ali Sorayyaei; Mohamad, Norhisham Binti; Ramli, Rusyaizila Binti; How, Chin Si (Journal of Reviews on Global Economics, 2019)
Effective professional communication is required for the university students, particularly studying Education, to achieve their career goals. Perhaps a set of the most important skills for enhancing professional communication strategies among the university students and practitioners are to use Higher Order Thinking skills (HOTs). This research was conducted to investigate the Malaysian students’ attitude towards HOTs in their professional communication strategies at two private universities in Malaysia. It tried to analyse the implementation of HOTs to indicate if these skills are able to enhance the university students’ professional communication strategies in academic and professional settings. This study involved 54 respondents which consisted of 41 Bachelor of Teaching English as a Second Language (BTESL) students and 13 Diploma of TESL (DTESL) students already done their internship. The research instruments were questionnaire and interview. The researcher-designed questionnaire was distributed through online to all the respondents. Moreover, the interviewees were randomly selected by the researchers. Data were analyzed by using descriptive statistics and a comparative study. Overall, the findings showed that only a few trainee Malaysian BTESL students fell under the category of good background knowledge in HOTs. However, in the comparative study, it surprisingly showed that Malaysian DTESL students had a better understanding of HOTs compared to Malaysian BTESL trainee students. Therefore, it is suggested that HOTs are significant required thinking and creative skills which all Malaysian university students need to obtain during their education in the university level so that they can communicate effectively in this competitive world to achieve their career objectives.